On X–ray Source For Dual Wave Absorptiometry - Gogolev, A.; Chistyakov, S.; Filatov, N.; Shevelev, M.; Uglov, S.; Vukolov, A.
A new method for the formation of a dual X–ray source spectrum for the method of analyzing multiphase fluid flow based on wave dispersive X–ray absorptiometry using crystalline monochromators is proposed. The experimental results of testing the proposed method of forming the optimal X–ray spectrum are presented. A comparison with the results of numerical simulation is given.
Keywords: Physics; Optics